2006
DOI: 10.1007/s00267-006-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

Linkages Between Nutrients and Assemblages of Macroinvertebrates and Fish in Wadeable Streams: Implication to Nutrient Criteria Development

Abstract: We sampled 240 wadeable streams across Wisconsin for different forms of phosphorus and nitrogen, and assemblages of macroinvertebrates and fish to (1) examine how macroinvertebrate and fish measures correlated with the nutrients; (2) quantify relationships between key biological measures and nutrient forms to identify potential threshold levels of nutrients to support nutrient criteria development; and (3) evaluate the importance of nutrients in influencing biological assemblages relative to other physicochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
130
5
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 40 publications
16
130
5
3
Order By: Relevance
“…White et al (2001) and Ballard and Krueger (2005) reported that an increase in the duration of cattle presence in an area increased the amount of manure in that area. The high soil-nutrient concentrations resulting from the concentration of feces in congregation areas may be transported in precipitation runoff and negatively impact aquatic ecosystems (Reynoldson 1987;Belsky et al 1999;Wang et al 2007). As the previous results were observed from research conducted on Western rangelands, these findings may not be applicable to management of Midwestern pastures because of differences in rainfall, climate, forage and soil types, and management.…”
Section: Introductioncontrasting
confidence: 46%
“…White et al (2001) and Ballard and Krueger (2005) reported that an increase in the duration of cattle presence in an area increased the amount of manure in that area. The high soil-nutrient concentrations resulting from the concentration of feces in congregation areas may be transported in precipitation runoff and negatively impact aquatic ecosystems (Reynoldson 1987;Belsky et al 1999;Wang et al 2007). As the previous results were observed from research conducted on Western rangelands, these findings may not be applicable to management of Midwestern pastures because of differences in rainfall, climate, forage and soil types, and management.…”
Section: Introductioncontrasting
confidence: 46%
“…Authors of previous studies have reported similar threshold declines in macroinvertebrate richness as N and P concentrations increased (Wang et al 2007, Weigel and. Wang et al (2007) The similarity between the Central Plains and Wisconsin stream TN and TP threshold concentrations and correlation coefficients suggest a broad agreement in threshold values for the mid-continental US. These threshold nutrient concentrations could be used to develop nutrient criteria for this region, and might be combined with experimental data to gain a better understanding about the main factors driving the threshold relationships .…”
Section: Discussionmentioning
confidence: 99%
“…However, all water-quality variables were positively correlated, so nutrient effects were difficult to separate from turbidity or sedimentation effects. Wang et al (2007) determined that nutrients accounted for only 22% of the variation explained by environmental factors in their study of benthic macroinvertebrate patterns across water-quality gradients. Catchment features, such as watershed area, and instream habitat features, such as silt substrate or embeddedness, explained ,42% of the variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations